An exploratory study of customer satisfaction towards homestay programme in Kampung Pulai, Melaka / Sofinah Yussoff - Yussoff, Sofinah (Faculty of Business and Management, 2009)
Satisfaction is the customers' evaluation of a product or service in terms of whether product or service has met their expectations. Although satisfying customers may not be the ultimate goal for business, customer satisfaction is essentially associated with the financial performance. Therefore, it is important to understand customer expectation in purpose to deliver the right products or services over time. This research is about an exploratory study of customer satisfaction towards Homestay Programme in Kampung Pulai, Melaka. Service attributes are terms to be studied which includes programme, activities, facilities, food, service provider, place, and amenities and be investigated whether or not those attributes have significant relationship with customer satisfaction.